Blood pressure in free-ranging gray wolves (Canis lupus) immobilized with tiletamine and zolazepam - Malmsten, Jonas (SLU/Dept. of Clinical Sciences (until 231231), 2007)
This study aims to evaluate blood pressure measurements in immobilized free-ranging gray wolves (Canis lupus) in Sweden. Eight immobilized wolves (five adults and three juveniles) were included in this study. All wolves were darted from a helicopter with darts containing 250 milligrams of tiletamine and 250 milligrams of zolazepam. Immobilized wolves that showed signs of arousal, recieved a supplemental intramuscular injection of medetomidine. Systolic and diastolic blood pressure was measured non-invasively with an oscillometric device (Memoprint®, MediVet, Babenhausen, Germany) designed for dogs and cats. Rectal temperature, heart rate and respiratory rate were also measured. The hypothesis is that the wolves develop hypertension as a result of helicopter pursuit and the drug used. Three wolves were normotensive, four wolves had a moderate diastolic hypertenstion at one or more measuring point, and one wolf had a severe diastolic hypertension together with a mild systolic hypertension. None of the wolves had a moderate or a severe systolic hypertension. In conclusion, the effect on blood pressure was not as severe as previously thought. It was also noted that wolves who recieved an injection of medetomidine had a better anesthesia. In addition to this, other reference values for blood pressure and heart rates for free-ranging gray wolves should be used in future studies. Studien avsåg att utvärdera blodtrycket hos immobiliserade frilevande vargar (Canis lupus) i Sverige. Hypotesen är att de sövda vargarna får hypertension av helikopterjakten och tiletamin. Åtta vargar (fem vuxna och tre valpar) ingick i studien. Vargarna sövdes från helikopter med bedövningspilar innehållande 250 mg tiletamin och 250 mg zolazepam, motsvarande 10,6 – 21,3 mg/kg. De vargar som under sövningen uppvisade tecken på att vakna, fick en intramuskulär injektion medetomidin motsvarande doser på 0,016 – 0,0625 mg/kg. Systoliskt och diastoliskt blodtryck mättes icke-invasivt med en oscillometrisk apparat (Memoprint, MedVet, Babenhausen, ...